2018
DOI: 10.1016/j.ijmedinf.2018.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Challenges optimizing the after visit summary

Abstract: Background: The after visit summary (AVS) is a paper or electronic document given to patients after a medical appointment, which is intended to summarize patients' health and guide future care, including self-management tasks. Objective: To describe experiences of health systems implementing a redesigned outpatient AVS in commercially available electronic health record (EHR) systems to inform future optimization. Materials and Methods: We conducted semi-structured interviews with information technology and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Research has found that patient needs vary based on health contexts of chronic illness vs acute medical situations, and longitudinal primary care vs specialty care. 26,27 Current solutions provided by EHR vendors may not meet the needs of patients, caregivers, or providers. 26 Health care providers have the opportunity to push the development of health care visit summaries tailored to patient learning styles, incorporating technological solutions such as audio and video to supplement printed materials.…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that patient needs vary based on health contexts of chronic illness vs acute medical situations, and longitudinal primary care vs specialty care. 26,27 Current solutions provided by EHR vendors may not meet the needs of patients, caregivers, or providers. 26 Health care providers have the opportunity to push the development of health care visit summaries tailored to patient learning styles, incorporating technological solutions such as audio and video to supplement printed materials.…”
Section: Discussionmentioning
confidence: 99%
“…This was intended to empower patients and encourage self-management by helping them to understand their health, but AVS documents are often long, poorly laid out, and contain a lot of medical jargon. Clinicians and patients have attempted to improve the layout and readability of these documents, and to incorporate the type of plain language that is used in patient addressed letters; however, the inflexible architecture of electronic health records makes it difficult to implement these improvements 12…”
Section: How Do Letters Affect Patient Autonomy?mentioning
confidence: 99%
“…Subheadings can help with clinical coding of the information22 but using too many headings in a “pro forma” layout makes the letter impersonal and harder to read 12…”
Section: How Do You Write Letters To Patients?mentioning
confidence: 99%
“…In addition, young people may have different levels of ICT literacy, which may deteriorate with heavy workloads and tiredness. Managers may also need to keep in mind that digitization has not always been handled in ideal ways [5][6][7][8][9]. We are awaiting a comparison between data from our hospitals and data from Freiburg.…”
Section: Isase 2019 Isasementioning
confidence: 99%
“…Although various advantages of digitization have been reported, such as access to information that brings added value in increasing usage and health information exchange, consideration for older professionals was also mentioned in terms of skills needed to use the system [8]. Electronic health records are also reported to have some limitations in optimizing after visit-summaries [9]. However, well-trained nurses showed relatively high rates of ICT manipulation [10].…”
Section: Introductionmentioning
confidence: 99%